Benefits and costs of climate change mitigation technologies in paddy rice: Focus on Bangladesh and Vietnam - Basak R (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
This report examines the costs and benefits of alternate wetting and drying (AWD) in paddy rice production in Bangladesh and Vietnam as a technology that can lead to reduced greenhouse gas (GHG) emissions. AWD is a systematic management practice that involves periodic drying and reflooding of rice fields. Similar water management practices in rice growing have been used in Asian countries for decades, although not optimized for GHG reduction (Richards and Sander 2014). This report reviews the literature and examines the potential costs and benefits of implementing AWD at national scales in Bangladesh and Vietnam, two countries with current interest in promoting large-scale adoption of AWD. The report summarizes the wealth of information on the agronomic benefits of AWD, yet finds very little evidence of AWD’s economic impacts, especially in conjunction with impacts on GHG emissions. The analysis provides a synthesis of the costs and benefits of AWD (e.g., production costs, revenues, yields, other benefits) on a per-hectare basis and a preliminary estimate of the technology’s national-level impacts and implementation costs. It must be noted that only one study could be found on the production costs of AWD in Vietnam; thus more representative cost data would be required. Program implementation costs were estimated based on information found in the budgets from a relevant Nationally Appropriate Mitigation Action program in the Philippines and other agriculture sector technical assistance projects Existing evidence and expert opinion indicate that AWD is very promising in terms of its potential to increase farmers’ yields and profits and GHG reduction potential in Bangladesh and Vietnam. Adoption of AWD may allow for additional profit for farmers of between $100 and $400/ha as well as a reduction of 0.8 to 4 tCO2e/ha. The increased profit is due to decreased irrigation costs and increased yields from the use of AWD.